The architectural void in the Arabian Peninsula between the opinions of European researchers and historical and archaeological facts - Zayer, Salahaldin Muhsin (Al-Adab Journal, 2022)
K says. Criswell: (It seems that the Arabs before Islam had only simple concepts of building, and that their Kaaba before the year (608 AD) was no more than four walls as high as a person’s height and surrounding the sacred well of Zamzam, and that in the early days of Islam they did not bring any Islamic architecture to the conquered country Except for what serves the requirements of their prayers.At this time, nine-tenths of the population were nomadic Bedouins who saw the finest Islamic architecture in a camel's hair tent....in other words, the Arabian Peninsula constituted an almost complete architectural void(.In this research, we will discuss the presentation of some information that came in the historical and archaeological sources and references that confirm that the Arabs before Islam had architecture in the Arabian Peninsula, the first part of which is what is visible until now, such as the Kaaba in Makkah Al-Mukarramah, and the Prophet’s Mosque in Al-Madinah Al-Munawwarah , and many cities and buildings that were distributed over the countries in the Arabian Peninsula.And the other section of Arab architecture before Islam became a trace after an eye, and the historical sources included many of them in the folds of books.Through research, we concluded that Professor Criswell's statement now needs to be reconsidered by researchers and specialists to clarify the civilized reality of the Arabs before and after Islam, and to reveal the remaining effects that reflect the originality of Arab and Islamic architecture.